Ultrasound Findings in Hand Joints Involvement in Patients with Psoriatic Arthritis and Its Correlation with Clinical DAS28 Score - Priyanka Naranje; Mahesh Prakash; Aman Sharma; Sunil Dogra; Niranjan Khandelwal (Radiology Research and Practice)
Objective. To determine the frequency of the various ultrasound findings in hand joints in patients with psoriatic arthritis and correlate grayscale and Power Doppler ultrasonography findings with Disease Activity Score 28. Methods. This prospective study was performed in 30 patients. Ultrasound evaluation of 28 joints of both hands was undertaken and various findings were recorded including synovial hypertrophy, Power Doppler abnormality, soft tissue thickening, tendonitis, joint effusion, periosteal reaction, and erosions. Composite ultrasound scores and Disease Activity Score 28 were calculated and compared. Spearman correlation was used to see relationship between the ultrasound and DAS28 scores. Results. Ultrasound detected more abnormalities in the hand joints than did clinical examination. The frequency of various ultrasound abnormalities was as follows: Synovial hypertrophy was seen in 100%, Power Doppler abnormality suggesting hypervascularity was seen in 36.7%, soft tissue thickening was seen in 66.7%, periosteal reaction was seen in 33.3%, erosions were seen in 30% (mostly in DIP and PIP joints), and flexor tendonitis was seen in 6.7% of patients. Significant correlation was found between Disease Activity Score 28 and grayscale joint score (GSJS) (Spearman’s ρ: 0.499; P: 0.005), grayscale joint count (GSJC) (ρ: 0.398; P: 0.029), and Power Doppler joint score (PDJS) (ρ: 0.367; P: 0.046). There was a statistically significant difference between remission and low disease activity group and moderate disease activity group in terms of GSJC, GSJS, PDJC, and PDJS (P<0.05). These ultrasound measures were higher in moderate disease activity zone patients. Conclusion. Ultrasound is a useful modality for the objective assessment of psoriatic arthritis. Ultrasound including Power Doppler can be used as a modality for assessment of severity of psoriatic arthritis as it correlates with the clinical scoring.